The Effect of the Use of Respirators for Decreasing the Subjective Symptoms Disorders in the Center Nerve System in Digital Printing Printing Workers in Medan City - Tony Wibowo; Gerry Silaban; Taufik Ashar (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Workers who are exposed to evaporated organic compound from printing in the long term will have the risk for subjective symptom of central nervous system disorder in which it is the main entrance to the body through inhalation process. Workers in the production unit will have the most dominant risk for it. The objective of the research was to analyze the influence of using respirator on subjective symptom of central nervous system disorder in worker who work at digital printing industry. The research used one group pretest-posttest design. The samples were workers, taken by using purposive sampling technique. Bivariate analysis used paired t-test at the significance level of 95% (α=0.05). The result of the research showed that p-value = 0.0001 (p<0.05) which indicated that there was significant difference in the scores of Q16 questionnaires between pre and post intervention. The result of Q16 questionnaire in Swedish version showed that 20 respondents (100%) had difficulty breathing and 20 respondents (100%) had headache at least once a week. In the post-intervention with using respirators in one month, there was no complaint anymore. Respirator is equipped with organic vapor cartridge which is able to absorb gas from contaminated air before it enters the workers’ respiratory system. Using respirator as a personal protective device influences the decrease in subjective symptom of central nervous system disorder in printing workers. Using filter, cartridge, or tube in respirator should be done accurately otherwise it will cause danger for the workers.